Better Lucky Than Clever - Pedro Custódio, MD; Mark Westwood, MA, MD (JACC: Case Reports, 2023)
With an ever-expanding field of advanced cardiac imaging, clinicians tend to underestimate the importance of a detailed clinical history in reaching the correct diagnosis. This case illustrates 1 such example. (Level of Difficulty: Intermediate.)